Turnover Intentions and Political Influence Behavior : A Test Of Fight/Flight Responses to Organizational Injustice - A. Ansari, Mahfooz (2005)
We examined the role of organizational frustration as a linking mechanism between the perception of organizational injustice and fight (political influence behavior)/flight (turnover intentions) responses. The participants were 201 middle-level manager drawn from manufacturing and logistic companies in northern Malaysia. Data were collected by means of a structured questionnaire. Whereas all the three elements of injustice--procedural, distributive, and interpersonal-had significant positive impact on turnover intentions and political influence behavior, only procedural injustice and distributive injustice had such impact on frustration. Organizational frustration played a partial mediating role in the relationship of distributive and procedural injustice with turnover intentions and political influence behavior. Implications of the findings and directions for future research are suggested.